The World Trade Center Attack Disaster preparedness: health care is ready, but is the bureaucracy? - Mattox, Kenneth (BioMed Central, 2001)
When a disaster occurs, it is for governments to provide the leadership, civil defense, security, evacuation, and public welfare. The medical aspects of a disaster account for less than 10% of resource and personnel expenditure. Hospitals and health care provider teams respond to unexpected occurrences such as explosions, earthquakes, floods, fires, war, or the outbreak of an infectious epidemic. In some geographic locations where natural disasters are common, such as earthquakes in Japan, such disaster practice drills are common. In other locations, disaster drills become pro forma and have no similarity to real or even projected and predicted disasters. The World Trade Center disaster on 11 September 2001 provides new information, and points out new threats, new information systems, new communication opportunities, and new detection methodologies. It is time for leaders of medicine to re-examine their approaches to disaster preparedness.